Effects of Acute Hypoxic Stress on Physiological and Hepatic Metabolic Responses of Triploid Rainbow Trout (Oncorhynchus mykiss) - Han, Buying; Meng, Yuqiong; Tian, Haining; Li, Changzhong; Li, Yaopeng; Gongbao, Caidan; Fan, Wenyan; Ma, Rui (Frontiers in Physiology, 2022)
This experiment simulated the hypoxic environment caused by actual production operations in fish farming (i.e., catching, gathering, transferring, and weighting) to study the effects of acute hypoxic conditions on the physiological and metabolic responses of triploid rainbow trout (Oncorhynchus mykiss). Two groups of fish weighting 590 g were sampled in the normoxia group (dissolved oxygen above 7 mg/l) and hypoxia group (dissolved oxygen ranged from 2 to 5 mg/l for 10 min). The results showed that (1) regarding stress response, hypoxia increased plasma levels of cortisol, heat shock protein 70 (HSP-70), lysozyme, alanine aminotransferase (ALT), aspartate aminotransferase (AST) and creatine phosphokinase (CPK); induced the expression of hepatic genes encoding nuclear factor erythroid 2 related factor 2 (Nrf2), interferon γ (IFN-γ) and interleukin-1β (IL-1β). (2) Regarding metabolism response, hypoxia increased plasma levels of globulin (GLOB), glucose (GLU), triglyceride (TG) and lactate dehydrogenase (LDH); upregulated the hepatic gene expression of phosphoenolpyruvate carboxykinase, (PEPCK), pyruvate dehydrogenase kinase (PDK1), acetyl-CoA carboxylase (ACC) and acetyl-CoA oxidase (ACO); downregulated the hepatic gene expression of carnitine palmitoyl transferase 1 (CPT1); and unchanged the expression of hepatic genes in glycolysis and autophagy. (3) In response to hypoxia-inducible factors (HIFs), the hepatic HIF-2α gene was activated in the hypoxia group, but HIF-1α gene expression remained unchanged. Thus, during acute hypoxic stress, triploid rainbow trout were in a defensive state, with an enhanced immune response and altered antioxidant status. Additionally, the hepatic mitochondrial oxidation of glucose- and lipid-derived carbon in trout was suppressed, and hepatic gluconeogenesis and lipid synthesis were activated, which might be regulated by the HIF-2α pathway.